Best Paper Award - Voutsa, Maria C. (My University, 2026)
This award is proudly presented to Maria Voutsa, Nicolas Tsapatsoulis, Constantinos Djouvas, and Christiana Andreou in recognition of their outstanding paper entitled “Bias in the Machine: Cross-Model Evaluation of ChatGPT-4 and Qwen in Hotel Booking Review Annotation.” Presented at the 20th International Workshop on Semantic and Social Media Adaptation & Personalization (SMAP 2025), this paper was selected for its exceptional contribution to the field, demonstrating remarkable originality, scientific rigor, and methodological excellence. The work offers significant insights into bias analysis across large language models, advancing the understanding of semantic technologies and their application in social media adaptation and personalization systems.
Keywords: Sciences